Long Non-coding RNA GAS5 Worsens Coronary Atherosclerosis Through MicroRNA-194-3p/TXNIP Axis - Yanbing Li; Yu Geng; Boda Zhou; Xuejiao Wu; Ou Zhang; Xiaonan Guan; Yajun Xue; Siyuan Li; Xianjing Zhuang; Jie Zhou; Meng Chang; Guobin Miao; et al. (Molecular Neurobiology, 2021)
It is formerly conducted that long non-coding RNA growth arrest-specific 5 (GAS5) is involved in the process of coronary atherosclerosis (AS). The regulatory effects of GAS5 on the microRNA (miR)-194-3p/thioredoxin-interacting protein (TXNIP) axis in AS have been insufficiently explored yet. Thereafter, this work is started from GAS5/miR-194-3p/TXNIP axis in AS. AS rats were modeled to obtain their coronary vascular tissues and endothelial cells (ECs), in which GAS5, miR-194-3p, and TXNIP expression were tested. ECs were identified by immunohistochemistry. The mechanism among GAS5, miR-194-3p, and TXNIP was determined. ECs were transfected with inhibited GAS5 or overexpressed miR-194-3p to decipher their functions in proliferation and apoptosis of ECs in AS. Raised GAS5 and TXNIP and degraded miR-194-3p expression levels exhibited in AS. GAS5 bound to miR-194-3p while miR-194-3p targeted TXNIP. Depleting GAS5 or restoring miR-194-3p enhanced proliferation and depressed apoptosis of ECs in AS. This work clearly manifests that inhibited GAS5 facilitates the growth of ECs through miR-194-3p-targeted TXNIP in AS, consolidating the basal reference to the curing for AS.